Fabrication and characterization of curcumin loaded ovalbumin nanocarriers and bioactive properties - Akman, Perihan Kubra; Bozkurt, Fatih; Tornuk, Fatih (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
In this study, curcumin loaded ovalbumin nanoparticles (CONPs) were fabricated at optimized processing conditions and compared with the neat ONPs. The particles were characterized for molecular, thermal, antimicrobial, and antioxidant properties. The particle size values varied from 45.64 nm to 138.14 nm and the encapsulation efficiency of the CONP was 24%. SEM images indicated that ONPs and CONPs had spherical shapes and the particle diameters and size distributions were in accordance with the DLS measurement results. Fabrication of CONPs provided better (P < 0.05) inhibition on test pathogens as compared to pure curcumin, which demonstrates that particle size reduction of curcumin positively influenced its antibacterial efficiency. It was also clear that nanoencapsulation of curcumin significantly (P < 0.05) increased its antioxidant activity, suggesting that the curcumin/ovalbumin nanoencapsules could achieve similar antioxidant effect at much lower curcumin concentrations. FTIR results showed that curcumin was entrapped inside the ovalbumin nanocarriers successfully. According to DSC measurements, the melting temperature of ovalbumin did not change by curcumin encapsulation. In conclusion, the results suggested that ONPs could be an available carrier for encapsulation of curcumin at nano scale and had the potential to be used in the food industry and other bioactive delivery systems.
Keywords: bioactive delivery systems; nanotechnology; food science and technology; NANOPARTICLES; ANTIOXIDANT; NANOENCAPSULATION; ENCAPSULATION; FORMULATION; MECHANISM; DELIVERY; Food Science & Technology